Novel Biology of Tachykinins in Gonadotropin-Releasing Hormone Secretion - Leon, Silvia; Navarro, Víctor M. (Seminars in Reproductive Medicine, 2019)
The tachykinin family of peptides, composed of the neurokinins A and B (NKA, NKB) and substance P are involved in the central control of gonadotropin-releasing hormone (GnRH) release through a variety of neuronal circuitries that mediate the activation of Kiss1 neurons and the synchronization of their activity within the arcuate nucleus. The major outcome of this role is the precise regulation of the pulsatile pattern of GnRH release. In addition, tachykinins are involved in the maturation of the reproductive axis by determining the optimal timing of puberty onset, as well as in the timing of the preovulatory luteinizing hormone surge in females. Therefore, the action of tachykinins in reproduction appears to extend to all the critical aspects required for the successful attainment and maintenance of fertility. In this review, we summarize the latest advances in our understanding of the biology of tachykinins in the control of GnRH release, addressing the existing controversies, open questions, and future perspectives.
Keywords: tachykinins; GnRH; kisspeptin; hypothalamus; reproduction